Differentiate responses of soil nutrient levels and enzymatic activities to freeze-thawing cycles in different layers of moss-dominated biocrusts in a temperate desert - Zhang, Qing; Li, Jiwen; Zhang, Shujun; Li, Yonggang; Wu, Nan; Zhou, Xiaobing; Yin, Benfeng; Zhang, Yuanming (Frontiers in Plant Science, 2023)
Introduction The biological soil crust, a widespread phenomenon in arid and semi-arid regions, influences many ecological functions, such as soil stability, surface hydrology, and biogeochemical cycling. Global climate change has significantly altered winter and spring freeze-thaw cycles (FTCs) in mid and high-latitude deserts. However, it is unclear how these changes will affect the biological soil crust and its influence on nutrient cycling and soil enzyme activity. Methods We conducted this study in the Gurbantunggut Desert, a typical temperate desert, using the moss crust as an example of an evolved biological soil crust. Simulating the effects of different FTC frequencies (0, 5, and 15 times) on soil carbon, nitrogen, phosphorus-related nutrients, and extracellular enzyme activities allowed us to understand the relationship between soil environmental factors and nutrient multifunctionality during FTC changes. Results The results showed that recurrent FTCs significantly increased the accumulation of carbon and phosphorus nutrients in the soil and decreased the effectiveness of nitrogen nutrients. These changes gradually stabilized after 15 FTCs, with available nutrients showing greater sensitivity than the previous full nutrient level. FTCs inhibited carbon, nitrogen, and phosphorus cycle-related hydrolase activities and promoted carbon cycle-related oxidase activities in the crust layer. However, in the 0–3 cm layer, the carbon and phosphorus cycle-related hydrolase activities increased, while peroxidase and urease activities decreased. Overall, the nutrient contents and enzyme activities associated with the carbon, nitrogen, and phosphorus cycles were lower in the 0–3 cm layer than in the crust layer. In addition, the multifunctionality of nutrients in the soil decreased after 15 FTCs in the crust layer and increased after 5 FTCs in the 0–3 cm layer. Structural equation modeling showed that FTC, soil water content, pH, available nutrients, and extracellular enzyme activity had opposite effects on nutrient multifunctionality in different soil layers. The change in nutrient multifunctionality in the crust layer was primarily caused by changes in total nutrients, while soil water content played a greater role in the 0–3 cm layer. Regardless of the soil layer, the contribution of total nutrients was much higher than the contribution of available nutrients and extracellular enzyme activity. In conclusion, it is essential to consider different soil layers when studying the effects of global climate change on the nutrient cycling of the biological soil crust.